Tricks and tips for target volume definition and delineation in breast cancer: Lessons learned from ESTRO breast courses. (September 2021) - Kaidar-Person, Orit; Offersen, Birgitte V.; Boersma, Liesbeth; Meattini, Icro; Dodwell, David; Wyld, Lynda; Aznar, Marianne; Major, Tibor; Kuehn, Thorsten; Strnad, Vratislav; Palmu, Miika; Hol, Sandra; et al.
Abstract: Delineation of target and 'organ at risk' volumes is a critical part of modern radiation therapy planning, the next essential step after deciding the indication, patient discussion and image acquisition. Adoption of volume-based treatment planning for non-metastatic breast cancer has increased greatly along with the use of improved planning techniques, essential for modern therapy. However, identifying the volumes on a planning CT is no easy task. The current paper is written by ESTRO's breast course faculty, providing tricks and tips for target volume definition and delineation for optimal postoperative breast cancer irradiation.